THE IMPORTANCE OF CORPORA IN TRANSLATION TEACHING ANALYSIS («CONTEMPORARY TECHNOLOGIES OF COMPUTATIONAL LINGUISTICS», 2024)
Translation analysis involves examining and interpreting text in one language and accurately conveying its meaning in another language. To enhance the accuracy and efficiency of this process, many translators and linguists have turned to corpora – large collections of texts carefully selected and organized for linguistic research purposes. Incorporating corpora into translation analysis lessons can provide valuable insights and help improve translation quality.This article is devoted to give information with some examples of how corpora are utilized in translation analysis lessons.
Keywords: corpus analysis, Contextual Understanding, Terminology Research, Style and Register, Error Analysis, Quality Assurance, Cultural Considerations.